IN VITRO ANTIOXIDANT ACTIVITY AND FOURIER TRANSFORM INFRARED ANALYSIS OF ELAEAGNUS CONFERTA ROXB. LEAF EXTRACT - LALITHA G; TH, NAZEEMA (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The objective of this study was to carry out the antioxidant potential of Elaeagnus conferta (EC) Roxb. leaves that were worked on various assay 2,2-diphenyl-1-picrylhydrazyl hydrate (DPPH) and 2,2’-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) radical cation decolorization, total reducing power was studied by ferric reducing antioxidant power (FRAP) and total radical trapping antioxidant potential (TRAP) method. The spectroscopic technique Fourier transform infrared (FTIR) spectrophotometer was performed to detect the characteristic peak values and their functional groups of EC Roxb. Methods: Ethanol solvent is used ABTS, DPPH, FRAP, TRAP, and FTIR analysis. Results: ABTS assay, IC50 value was found to be 60 μg/ml compared with standard ascorbic acid 64 μg/ml. DPPH IC50 value of EC Roxb. compared with standard ascorbic acid was found to be 0.43 μg/ml and 0.62 μg/ml. FRAP IC50 value along with standard ascorbic acid was found to be 0.582 μg/ml and 0.596 μg/ml. The IC50 value of TRAP along with standard ascorbic acid was found to be 0.39 μg/ml and 0.62 μg/ml. In FTIR spectroscopic study, it revealed different characteristic peak values with various functional compounds such as phenols, alcohols, amide, alkanes, carboxylic acids, alkenes, primary amines, aromatics, ester, alkyl halides, and aliphatic amines compounds. Conclusion: EC Roxb. leaves have a potent rich source of antioxidant. In FTIR analysis, it is confirmed with the presence of phenolic compounds that can be emphasized for efficacy in pharmaceutics.